Manajemen dalam Perspektif Islam - Febriansyah, Muhammad Raihan; Bahri, Saiful (EduInovasi: Journal of Basic Educational Studies, 2024)
This research examines management concepts from an Islamic perspective based on the Al-Quran, Hadith, and other sources of Islamic teachings. Specifically, this research focuses on three main aspects, namely the concept of POAC (Planning, Organizing, Actuating, Controlling) in Islamic management, the success story of Rasulullah SAW in applying Islamic management principles during the Khandak War, and the implementation of Islamic management values in the world of education and its challenges and opportunities. Through a qualitative approach using literature study methods, this research explores the Islamic principles and values ​​that underlie management concepts, as well as studying the example of the Prophet Muhammad in management practices based on Islamic teachings. Apart from that, this research also analyzes the application of Islamic management values ​​in the educational context and identifies supporting and inhibiting factors in its implementation. It is hoped that the findings of this research will provide new insight into the development of management science based on Islamic values, as well as become a reference for management practices that are more dignified and in accordance with the guidance of Islamic teachings, both in educational institutions and other organizations.